ShareDisk: A novel visual tool to assess perceptions about who should be responsible for supporting persons with mental health problems. (June 2020) - Iyer, Srividya N; Pope, Megan A; Jordan, Gerald; Mohan, Greeshma; Loohuis, Heleen; Ramachandran, Padmavati; Rangaswamy, Thara; Malla, Ashok K
Objectives: Views on who bears how much responsibility for supporting individuals with mental health problems may vary across stakeholders (patients, families, clinicians) and cultures. Perceptions about responsibility may influence the extent to which stakeholders get involved in treatment. Our objective was to report on the development, psychometric properties and usability of a first-ever tool of this construct. Methods: We created a visual weighting disk called 'ShareDisk', measuring perceived extent of responsibility for supporting persons with mental health problems. It was administered (twice, 2 weeks apart) to patients, family members and clinicians in Chennai, India ( N  = 30, 30 and 15, respectively) and Montreal, Canada ( N  = 30, 32 and 15, respectively). Feedback regarding its usability was also collected. Results: The English, French and Tamil versions of the ShareDisk demonstrated high test–retest reliability ( r s = .69–.98) and were deemed easy to understand and use. Conclusion: The ShareDisk is a promising measure of a hitherto unmeasured construct that is easily deployable in settings varying in language and literacy levels. Its clinical utility lies in clarifying stakeholder roles. It can help researchers investigate how stakeholders' roles are perceived and how these perceptions may be shaped by and shape the organization and experience of healthcare across settings.